Personality-situation transactions from adolescence to old age. [article]. - Wrzus, Cornelia
People presumably choose and create their daily environments according to their personality. Prior research shows that, for example, more extraverted people engage more often in social situations, and more conscientious people engage more often in work-related activities compared with less extraverted or less conscientious people, respectively. The current study examined such personality-situation transactions in people's daily life. Based on the assumption that older people know themselves and their personality better than younger people, we investigated whether momentary and proximate personality-situation associations (i.e., changing from 1 type of situation into another) increase with older age. Three-hundred and 78 people aged 14 to 82 years described their Big Five traits and took part in a 3-week experience-sampling phase. Using mobile-phone based assessments in daily life, participants reported on average 55 times on their momentary situation. Multilevel modeling results showed that personality-situation associations varied with the age of participants. Some of the "established" personality-situation associations, such as for extraversion and time spent with friends or conscientiousness and time spent with work activities, were only observed in adolescence and young adulthood. In contrast, other personality-situation associations appeared only in late adulthood, such as for openness and time spent with friends. Yet most personality-situation associations did not vary significantly with people's age. In addition, personality traits predicted maintaining or entering personality-congruent situations. The latter results point to the active role of personality in shaping one's environment. The findings imply that some personality-situation transactions may be largely similarly across the life span. -- (from the authors)